Primary coronary stent implantation is a feasible bridging therapy to surgery in very low birth weight infants with critical aortic coarctation. (15th June 2018) - Stegeman, Raymond; Breur, Johannes M.P.J.; Heuser, Jörg; Jansen, Nicolaas J.G.; de Vries, Willem B.; Vijlbrief, Daniel C.; Molenschot, Mirella M.C.; Haas, Felix; Krings, Gregor J.
Abstract: Background: Surgical treatment of critical aortic coarctation (CoA) is difficult in very low birth weight (VLBW) infants ≤1500 g and preferably postponed until 3 kg with prostaglandins (PGE). Objectives: To investigate the procedure and outcome of primary coronary stent implantation as bridging therapy to surgery in VLBW infants with CoA. Methods: Retrospective evaluation of primary CoA stenting in VLBW infants from 2010 to 2015. Results: Five VLBW infants with a median gestational age of 29 weeks (27–32) underwent primary CoA stenting. Indication was cardiac failure in 4 and severe hypertension in 1 patient. Age and weight at intervention were 14 days (range 12–16) and 1200 g (680–1380), respectively. Stent diameter ranged 3–5 mm. The femoral artery used for intervention was occluded in all infants without clinical compromise. Severe restenosis and aneurysm occurred in 1 VLBW infant and was successfully treated with covered coronary stents. Median age at surgical correction was 200 days (111–804) and weight 5500 g (4500–11, 400). No reinterventions were required during a median postoperative follow-up of 2.8 years (0.1–5.0). Neurodevelopmental outcomes were normal and comparable between patients and siblings (4/5 gemelli). Conclusions: Primary coronary stent implantation in VLBW infants with critical CoA is a feasible bridging therapy to surgery. Highlights: Stent implantation is feasible in VLBW infants with critical aortic coarctation. Primary stent implantation offers a significant bridging-to-surgery interval. This two-step strategy resulted in lower rates of mortality and recoarctation.